Pengaruh Tingkat Kesejahteraan, Upah Lembur Dan Motivasi Kerja terhadap Kinerja Karyawan (Studi pada Karyawan CV. Bina Makmur Plantation SUM-SEL) - Rendi Irwandi; Jajuk Herawati; Epsilandri Septyarini (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of the level of welfare, overtime pay, and work motivation on employee performance (Study on Employees of CV. Bina Makmur Plantation SUM-SEL). The population in this study included all 50 employees of CV Bina Makmur Plantation. While the sample specified as many as 50 employees. The sampling technique in this study was a non-probability sampling technique, namely saturated sampling "The technique of determining the sample when all members of the population are used as samples" and its distribution using simple random sampling. Based on the results of the study, it shows that the level of Welfare, Overtime Pay, and Work Motivation simultaneously have a positive and significant effect on Employee Performance.